What About Prospective Fist-Generation Students Before Their Transition to Higher Education? An Analysis on Students Their Demographic Characteristics, Educational Intentions, and Parental Expectations in Limburg - Gordin, Diane Roberta Nicole (Student Undergraduate Research E-journal!, 2019)
A great body of research demonstrated that first-generation students (FGS) face significant barriers while transferring to higher education. Contrary, not much is known about this subject in The Netherlands. Using statistical analysis, the research will offer a primary examination how this group of students are doing during high school (prospective FGS) in track havo and vwo before their potential transition to higher education in the province of Limburg (The Netherlands). The analysis will provide a regional insight into the demographic characteristics, parental expectations, and educational intentions of this group of students compared to their peers. The results show that prospective FGS differ in the distribution of track, their educational intentions and the educational expectations their parents have. These results can inform future policy changes to accommodate educational equity among all student during different phases of their education in Limburg.